2021
DOI: 10.3390/toxics9060123
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesized Iron Oxide Nanoparticles from Petroselinum crispum Leaf Extract Mitigate Lead-Acetate-Induced Anemia in Male Albino Rats: Hematological, Biochemical and Histopathological Features

Abstract: This study aimed to investigate the ameliorative effects of iron oxide nanoparticles (IONPs) prepared from leaf extract of Petroselinum crispum compared to those prepared using a chemical method in lead-acetate-induced anemic rats. Twenty rats were divided into four groups (five rats each). Throughout the experimental period (8 weeks), the rats in group 1 were not given any therapy. The rats in groups 2, 3 and 4 were given 400 ppm lead acetate orally for 2 weeks to make them anemic. Following that, these rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 59 publications
5
15
0
Order By: Relevance
“…As they are stable officers, they have an enticing future. In the present analysis, the biological efficacy of certain secondary metabolites as antioxidant, antimicrobial and antitumor was suggested for the filamentous fungi; this finding is in accordance with the observations of Chen et al (2011);El-Gazzar et al, (2021);El-Bahr et al (2021). In addition, the present investigation found that A. flavus was the most activate fungus similar with that reported with the observations of Tenguria & Khan's (2011).…”
Section: Discussionsupporting
confidence: 92%
“…As they are stable officers, they have an enticing future. In the present analysis, the biological efficacy of certain secondary metabolites as antioxidant, antimicrobial and antitumor was suggested for the filamentous fungi; this finding is in accordance with the observations of Chen et al (2011);El-Gazzar et al, (2021);El-Bahr et al (2021). In addition, the present investigation found that A. flavus was the most activate fungus similar with that reported with the observations of Tenguria & Khan's (2011).…”
Section: Discussionsupporting
confidence: 92%
“…Fresh fruits were washed with sterile distilled water. One hundred grams of each fruit sample were mixed with distilled water at the ratio of 1:1 ( w / v ) as described previously [ 69 , 70 ], then homogenized by using a mixer (Braun combimax 700 vital, Berlin, Germany). The obtained fresh juice was then centrifuged at 15,000 rpm for 30 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Then the sections were washed to grids made of copper or nickel. Post contrastation of the sections was determined 10 min 8% uranyl acetate and 5 min 0.7% lead citrate + 0.9% sodium citrate after drying for 15 min; sections were demonstrated in a TEM, by a JEOL 2100 TEM at 80 KV at EM Unit, Mansoura University, Egypt [61][62][63].…”
Section: Transmission Electron Microscope (Tem) Of Sec-f1mentioning
confidence: 99%